The Influence Of Physical Environment, Situational Leadership On Performance Through Work Motivation - Dina Ariyanti; Nancy Yusnita; Diganti Herdiyana (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Human resources are an asset for organizations and agencies, because humans are part of the elements in every organization that can trigger creativity. Without effective human resources, it will be impossible for the organization to achieve its goals.The analysis used to test the research hypothesis uses descriptive analysis and path analysis. The results of this study show that there arethere is a positive influence of the physical environment on work motivation, there is a positive influence of situational leadership on work motivation, there is a positive influence of the physical environment on teacher performance, there is a positive influence of situational leadership on teacher performance, there is a positive influence of work motivation on teacher performance, there is a direct influence of the physical environment on performance through work motivation, there is a direct influence of situational leadership on performance through work motivation.In an effort to improve teacher performance, management ensures that the physical work environment is adequate, and that situational leadership is supportive so that it can increase work motivation.